Upaya Peningkatan Kemampuan Guru Dalam Penulisan Karya Ilmiah Melalui Pelatihan Penelitian Tindakan Kelas Di Wilayah Binaan Kecamatan Kalidawir Kabupaten Tulungagung - Asrori Mustofa (Politeknik Kampar, 2023)
The aim of this research was to strive to improve teachers' abilities in writing scientific papers through classroom action research training in the target area of ??Kalidawir District, Tulungagung Regency. Training activities are carried out in three stages, namely: preparation stage, implementation stage and reporting stage. The implementation of this training can be said to be successful. The indicators that serve as benchmarks for the success of implementing this service activity are the achievement of the activity objectives, namely increasing teachers' understanding of PTK, increasing motivation in implementing PTK and teachers gaining direct experience in preparing PTK proposals. The results of the research are scientific work which is rarely done by teachers, especially in madrasas. On the other hand, teachers realize that one of their tasks is to develop their ideas in the field of education in the form of scientific work. This is likely caused by limited abilities in compiling scientific work. The implementation of this training can be said to be successful. The indicators that serve as benchmarks for the success of implementing this training activity are the achievement of the activity objectives, namely increasing teachers' understanding of PTK, increasing motivation in implementing PTK and teachers gaining direct experience in preparing PTK proposals. The indicators that show success in providing experience implementing PTK and reporting PTK results cannot yet be measured. This is because no participant has officially submitted a request for assistance in implementing and reporting PTK results. Further training activities can be strengthened by providing special assistance to MI teachers to carry out classroom action research so that they are able to make PTK reports properly and correctly.